Pembentukan Komunitas Masyarakat Pembuat Media Tanam dari Sampah Plastik Kresek - Wiwit Probowati; Ika Afifah Nugraheni; Suryadi Suryadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The focus of the community service program is the formation of communities that are committed to processing plastic rubbish materials into planting media (mediokres). Mediokres is a product of Sayidan Agro Media’s organizational innovation in Sleman, D.I. Yogyakarta, which is able to utilize plastic bag rubbish at the Final Disposal Site becomes a planting medium to replace soil. Mediokres has been widely marketed in Indonesia However, in the production process of mediokres, there is the obstacle, one of which is the supply of mediokres products which is slow compared to the large consumer demand. Therefore the formed mediokres community is able to help meet the mediokres stock both for ordering and stocking every month. So that consumer demand is fulfilled.